Harnessing filamentous phages for enhanced stroke recovery - Li, Yang; Yang, Kai-di; Kong, De-cai; Li, Xiao-meng; Duan, Hao-yu; Ye, Jun-feng (Frontiers in Immunology, 2024)
Stroke poses a critical global health challenge, leading to substantial morbidity and mortality. Existing treatments often miss vital timeframes and encounter limitations due to adverse effects, prompting the pursuit of innovative approaches to restore compromised brain function. This review explores the potential of filamentous phages in enhancing stroke recovery. Initially antimicrobial-centric, bacteriophage therapy has evolved into a regenerative solution. We explore the diverse role of filamentous phages in post-stroke neurological restoration, emphasizing their ability to integrate peptides into phage coat proteins, thereby facilitating recovery. Experimental evidence supports their efficacy in alleviating post-stroke complications, immune modulation, and tissue regeneration. However, rigorous clinical validation is essential to address challenges like dosing and administration routes. Additionally, genetic modification enhances their potential as injectable biomaterials for complex brain tissue issues. This review emphasizes innovative strategies and the capacity of filamentous phages to contribute to enhanced stroke recovery, as opposed to serving as standalone treatment, particularly in addressing stroke-induced brain tissue damage.